Limits of Reason in J.M. Coetzee’s The Schooldays of Jesus - Álvarez Sánchez, Patricia (Miscelánea: A Journal of English and American Studies, 2019)
This paper explores J.M. Coetzee’s latest novel, The Schooldays of Jesus (2016), and focuses on its intense dialogue with ancient philosophical ideas such as Plato’s Theory of Forms and some of the author’s literary precursors, such as Cervantes’ Don Quixote (1605) and Musil’s The Confusions of Young Törless (1906). It is also a tribute to Johann Sebastian Bach’s brilliant mind and music, which Coetzee has already commented upon on different occasions. The Schooldays is an intertextual story about the magic of numbers, dance and music and tells the story of Davíd, a rebellious child who is sent to Juan Sebastián Arroyo’s Academy of Dance (Arroyo is Bach’s name translated into Spanish), where he learns that music and dance can help us communicate with the universe and discover our true selves. It is the first time Coetzee incorporates magical elements and constant spiritual allusions in one of his plots, and I will argue that these, together with the intertextuality with other novels and texts and the characterization of the main characters, are used to show (once again) his ambivalence towards rationalism, but in a different style. This represents a turning point in his literary career.